THE RELATIONSHIP OF FAST FOOD CONSUMPTION WITH THE LEVEL OF PRIMARY DYSMENORHORE IN WAHID HASYIM BALUNG MA STUDENTS - Ma'isyatul Mukarromah (LPPM Universitas dr. Soebandi, 2024)
Dysmenorrheais pain felt during menstruation, it occurs in the uterus, hips, and waist. The cause of dysmenorrhea is a poor diet as an example of frequently eating fast food without paying attention to balanced nutritional intake. This research aims to understand the significance of the relationship between consuming fast food and the level of major dysmenorrhea in MA student Wahid Hasyim Balung. Method: This type of research carried out is correlational (relationship) to a cross-sectional approach. The total population in this study was 45 with a sample of 40 respondents. The sampling technique uses simple random sampling and data collection with questionnaires. Univariate analysis of frequency distribution as well as percentage, bivariate analysis of Spearman rank and Contingency Coefficient. Results: Most (55%) female students consumed fast food and nearly half (42.5%) experienced some degree of primary dysmenorrhea. From the analysis, P-value (0.004) < α (0.05) hereby H0 is rejected which means there is a relationship and the contingency coefficient test obtained a value of 0.455 which means the relationship is quite strong. Conclusions: there is an association of fast food consumption with the rate of primary dysmenorrhea. Advice for respondents is expected to limit consumption of fast food so as not to cause menstrual pain (dysmenorrhea).